2008
DOI: 10.1016/j.jorganchem.2007.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocenyl compounds possessing protected phenol and thiophenol groups: Synthesis, X-ray structure, and in vitro biological effects against breast cancer

Abstract: We have previously shown that conjugated ferrocenyl p-phenols show strong cytotoxic effects against both the hormone-dependent MCF-7 and hormone-independent MDA-MB-231 breast cancer cell lines, possibly via metabolic quinone methide (QM) formation. To further evaluate this proposed mechanism, we have created a series of ferrocenyl prodrugs containing methyl and acetyl-protected thio-and oxo-phenols: 2-ferrocenyl-1,1-bis(4-acetoxyphenyl)-but-1-ene (5), 2-ferrocenyl-1,1-bis(4-thioacetylphenyl)-but-1-ene (6), 2-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 41 publications
(40 reference statements)
1
20
0
1
Order By: Relevance
“…This result is in accord with that found for the sandwich or half-sandwich diphenol complexes of ruthenium, rhenium or manganese [26]. It also confirms that even compounds with low RBA values can express a significant estrogenic effect [27]. The aminoalkyl-hydroxycobaltifens, 2g and 2h, direct analogues of tamoxifen and ferrocifen, are weakly cytotoxic towards both cell lines.…”
Section: Cell Proliferationsupporting
confidence: 88%
“…This result is in accord with that found for the sandwich or half-sandwich diphenol complexes of ruthenium, rhenium or manganese [26]. It also confirms that even compounds with low RBA values can express a significant estrogenic effect [27]. The aminoalkyl-hydroxycobaltifens, 2g and 2h, direct analogues of tamoxifen and ferrocifen, are weakly cytotoxic towards both cell lines.…”
Section: Cell Proliferationsupporting
confidence: 88%
“…[2][3][4][5][6][7][8][9][10][11][12] We have shown that some ferrocene derivatives are very active against cancer cells. The addition of a ferrocenyl moiety to selected polyaromatic phenols, [13][14][15][16] amines, 17,18 amides, 19 and esters 19,20 can potentiate their antiproliferative effects against breast and prostate cancer cells. For example, 4-hydroxytamoxifen, the active metabolite of the breast cancer drug tamoxifen, 21 shows limited cytotoxicity against hormone-refractory breast cancer cells (LC 50 for MDA-MB-231 cells:…”
Section: Introductionmentioning
confidence: 99%
“…Nos últimos anos esta nova área de pesquisa tem despertado interesse, uma vez que a incorporação de metais de transição à estrutura de uma droga pode acentuar a sua atividade biológica. 22 25,26,27 O ferroceno 12 é um composto estável, 28,29 não-tóxico, 28 que exibe interessantes propriedades de oxiredução, 30 as quais se devem à sua capacidade de sofrer oxidação reversível, com a geração de espécie do tipo cátion-radical -íon ferrocênio 13. 28 14,37,40 Estudos mostraram também que além de não haver resistência cruzada entre a ferroquina e os demais antimaláricos quinolínicos, 40 a atividade de 14 independe das mutações dos genes do P. falciparum, o que não ocorre com a cloroquina.…”
Section: Estratégia Bioorganometálicaunclassified